Metallo-Beta-Lactamases: NDM - Leis, Kamil; Mazur, Ewelina; Szyperski, Paweł; Kaczor, Patryk; Kolan, Michalina; Wiśniewski, Bartłomiej; Jabłońska, Magdalena; Kulczyńska, Aleksandra; Baska, Aleksandra; Kazik, Jakub; Bojczuk, Daria; Grzelakowska, Klaudyna; et al. (Journal of Education, Health and Sport, 2019)
New Delhi, an enzyme belonging to the Metallo-beta-lactamases and Carbapenemases group, is most commonly found in Klebsiella pneumoniae and Escherichia coli. It determines these bacteria resistance to the majority of known antibiotics. NDM-1 was discovered in 2008 in a man treated in New Delhi for E. coli infection. Since the first appearance, 17 subtypes of this enzyme have been discovered. Its occurrence has been reported in Europe (Great Britain, France, Belgium - where even a national alert has been issued) as well as in the United States and in Africa. Most cases of New Delhi enzyme bacterial infections are reported in India or in people who have traveled to this country. There is no treatment method described so far. Therapy is based on antibiotic susceptibility test results. Colistin shows the highest effectiveness against NDM. There are also tests suggesting that Isomargololone and Nimbolide may be effective in most cases of NDM infection.